Plasmon absorption of infrared radiation in periodic structures Si/Si3N4/SiO2/Si/Al with window surface layer - Mukhammad, Asiya I.; Nalivaiko, Oleg Yu.; Kolos, Vladimir V.; Gaiduk, Peter I. (Journal of the Belarusian State University. Physics, 2024)
Transmission and reflection spectra of periodic window structures Si/Si3N4/SiO2/Si and Si /Si3N4/SiO2/Si/Al befor and after thermal annealing were obtained using Fourier transform infrared spectrometry. Experimental transmission and absorption spectra were studied in comparison with theoretical ones. Theoretical spectra were calculated using the finite difference time domain method. The theoretical transmission spectra are in good correlation with the experimental ones. It was found that after thermal annealing, the transmission level of the structure drops by 5–20 %. It has been shown that deposition of a 90 nm thick aluminium film on the back side of the structure does not affect the transmission level of the structure without annealing, but reduces the transmission level of the annealed structure by more than 20 %. It was noted that the absorption intensity of the n+-Si/poly-Si/Si3N4/SiO2/Si/Al structure does not fall below 70 % in the wavelength range of 2.5–9.0 μm. In this case, the intensity of the absorption peak at a wavelength of 4.3 μm is 87 %. It has been established that the appearance of absorption peaks at wavelengths of 4.3 and 8.0 μm in the absorption spectra of the annealed structure can be associated with the manifestation of plasmonic effects arising due to the periodicity of the structure.
Keywords: plasmonic absorption; periodic structures; absorption spectra; Fourier spectroscopy; doped silicon